Molecular Architecture of the Antiophidic Protein DM64 and its Binding Specificity to Myotoxin II From Bothrops asper Venom - Soares, Barbara S.; Rocha, Surza Lucia G.; Bastos, Viviane A.; Lima, Diogo B.; Carvalho, Paulo C.; Gozzo, Fabio C.; Demeler, Borries; Williams, Tayler L.; Arnold, Janelle; Henrickson, Amy; Jørgensen, Thomas J. D.; Souza, Tatiana A. C. B.; et al. (Frontiers in Molecular Biosciences, 2022)
DM64 is a toxin-neutralizing serum glycoprotein isolated from Didelphis aurita, an ophiophagous marsupial naturally resistant to snake envenomation. This 64 kDa endogenous antitoxin specifically targets myotoxic phospholipases A2, which account for most local tissue damage associated with viper snakebites. This study investigated the noncovalent complex formed between native DM64 and myotoxin II, a myotoxic phospholipase-like protein from Bothrops asper venom. Analytical ultracentrifugation, size exclusion chromatography, and small-angle X-ray scattering (SAXS) data indicated that DM64 is monomeric in solution and binds equimolar amounts of the toxin. Initial attempts to solve the structure of DM64 experimentally failed due to N-glycan heterogeneity and low recovery of heterologous protein. Classical molecular modeling techniques were impaired by the lack of templates with more than 25% sequence identity with DM64. An integrative structural biology approach was then applied to generate a refined three-dimensional model of the inhibitor bound to myotoxin II. The five immunoglobulin-like domains of DM64 were individually modeled using the I-TASSER suite. Distance constraints generated by cross-linking mass spectrometry of the complex guided the docking of DM64 domains to the crystal structure of myotoxin II (PDB ID 1CLP), using the Rosetta docking suite. The model of the DM64-myotoxin II complex was successfully fitted to a SAXS envelope. Inter-protein cross-links and limited hydrolysis analyses shed light on the inhibitor's regions involved with toxin interaction, revealing the critical participation of the first, third, and fifth domains of DM64. Our data showed that the fifth domain of DM64 binds to myotoxin II amino-terminal and beta-wing regions. The third domain of the inhibitor acts in a complementary way to the fifth domain. Their binding to these toxin regions precludes dimerization, presumably interfering with toxicity, which appears to be related to the quaternary structure of the toxin. The first domain of DM64 likely interacts with the functional site of the toxin putatively associated with membrane anchorage. We propose that both mechanisms concur to inhibit myotoxin II toxicity by DM64 binding. The present topological characterization of this toxin-antitoxin complex constitutes an essential step toward the rational design of novel peptide-based antivenom therapies targeting snake venom myotoxins.